Agama, Etnis dan Politik dalam Panggung Kekuasaan: Dinamika Politik Tauke Dan Kiai Di Madura - M. Imam Zamroni (el Harakah: Jurnal Budaya Islam, 2008)
This article aims to describe political movement of employer (tauke) and kiai in Madura showing a significant role of their economic and religious capitals that have become basic of political movement to influence their society. They try to install their power by participating in a certain political party for occupying strategic positions either in village or regional level. An effort building connections with others local elites becomes one of political strategies in occupying structural power. In the one hand, Tauke are non-indigeneous people as Chinese ethnic and the other hand kiai are indigenous people as Madurese, they are having different basic resources of power. In the some case, they combined the power as political strategy to appease local democratic election (Pilkada) in Pamekasan Madura. By paying attention in a tobacco trade case, the power relation among employer, trader and broker is actually oriented towards managing huge profit in process. Finally, within elite's perspective, capital economics, cultural, social, and religion are always operated in all matter. Artikel ini bertujuan untuk menggambarkan gerakan politik pengusaha (tauke) dan kiai di Madura yang menunjukkan peran penting ibu kota ekonomi dan agama mereka yang telah menjadi dasar gerakan politik untuk mempengaruhi masyarakat mereka. Mereka mencoba memasang kekuatan mereka dengan berpartisipasi dalam partai politik tertentu untuk menduduki posisi strategis baik di tingkat desa maupun di tingkat regional. Upaya membangun hubungan dengan elite lokal lainnya menjadi salah satu strategi politik dalam menduduki kekuatan struktural. Di satu sisi, Tauke adalah orang-orang non-indigeneous karena etnis Tionghoa dan di sisi lain kiai adalah penduduk asli orang Madura, mereka memiliki sumber daya dasar yang berbeda. Dalam beberapa kasus, mereka menggabungkan kekuatan tersebut sebagai strategi politik untuk menenangkan Pilkada di Pamekasan Madura. Dengan memperhatikan kasus perdagangan tembakau, hubungan kekuasaan antara pengusaha, pedagang dan broker sebenarnya berorientasi pada pengelolaan keuntungan besar dalam proses. Akhirnya, dalam perspektif elit, ekonomi modal, budaya, sosial, dan agama selalu dioperasikan dalam segala hal.